Suprimento de água no Teatro de Operações da Amazônia: Emprego tático de embarcações para coleta, tratamento e distribuição de água potável para tropas militares, em combate continuado, na Amazônia Ocidental - Resende, Rafael Lemos de (Universidade do Vale do Rio dos Sinos, 2011)
The present work approached the military logistics in Amazonia, analyzing the difficulties of collecting, treating and distributing drinkable water to the military troops during a continued combat in the region, more specifically in the occidental Amazonia area. The difficulty of the troops in finding appropriate water to drink was evaluated, verifying the importance of water regarding the troop supplying, since the lack of it impairs the maintenance of the military effectiveness. For doing this experiment, the characteristics of the region were approached and the way of making the supplying of water during a battle in such a peculiar place was analyzed, showing that one of the greatest obstacles is concentrated in supplying and transporting logistics functions, from receiving resources to their distribution. The importance that Amazonia has in the world context was analyzed, at this moment when there is the world depletion of freshwater sources. The research data were obtained through the bibliographic revision, the analyses of the scientific articles and the data collection made by applying questionnaires to the military personnel working in the Amazonia military organizations, or to those who have already served in that region. In the face of this concern, the relevancy of the theme was verified, noting that one of the ways of minimizing the issue may well be the tactical use of boats as water supplying movable stations, to collect, treat and distribute drinkable water to the military troops.
Keywords: Água; Logística militar; Amazônia; Water; Military logistic; Amazon